The effect of addition of bromelin enzyme in commercial feed on growth and survival rate of river catfish (Hemibagrus nemurus) seeds in cultivation of the recirculation system - Anggun Pratiwi; Niken Ayu Pamukas; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractEnzyme are a group of proteins that are abundant in living cells in have important functions as catalyst for biochemical reactions. The research was conducted for 50 days on 08 april - may 2019 at the laboratory of cultivation technology ,Faculty Of Fisheries And Marine,University Of Riau. The purpose of this research was yo determine the optimal dose of bromelin in feed in creasing grownt and survival rate of rivel catfish seeds. River catfish(Hemibagrus nemurus) seeds used in this research were obtained from fish formers in Bangkinang,Riau. The research contained used in the from an aquarium measuring 60 x 40 x 40 cm as many as 15 containers whit a stocking density of river catfish seeds 1 tail / 2,5 L of water. This research conducted experimentaly by using a compietely randomized desig (CRD) one factorial,whit five treatments and three replications. The treatment were the addition of bromelin enzyme on of feed commercial whit different doses of p1 : 2%/kg of feed, p2 : 3,5%/kg of feed, p3 : 5%/kg of feed, p4 : 6,5%/kg of feed, p5 : 8%/kg of feed. The result showed that the addition of bromelin in feed whit different doses. Significantly affected (P<0,05) on absolute weight, absolute lenght, spesific growth rate, and survival rate. The best growth was p2 treatment whit 6,98 grams absolute weight value, 4,99 cm absolute legth , 2,08 % specific growth rate, and 100% survival rate. Water quality in this research is still in the normal range of 27,5 - 29,9°C temperature, 6-7 pH, 6,1- 7,3 mg/L dissolved oxygen (DO), and 0,03- 0,09 mg/L ammonia. Keyword : river catfish, bromelin, growth